Some Theoretical Properties of a Two-Sector Model of Optimal Growth - Johansen, L. (Review of Economic Studies, 1967)
Journal Article Some Theoretical Properties of a Two-Sector Model of Optimal Growth Get access L. Johansen L. Johansen University of Oslo Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 34, Issue 1, January 1967, Pages 125–141, https://doi.org/10.2307/2296574 Published: 01 January 1967